(untitled) (Bangladesh Journal of Psychiatry, 2020)
Exposure to obstetric complication was known to be associated with development of psychiatric disorders. The aim of the study was to see the association of externalizing behaviors in children and adolescents with birth complications in a tertiary care hospital in Bangladesh. It was a cross sectional study conducted among 96 cases from July, 2018 to June, 2019. Birth complications and psychosocial adversity were assessed from hospital record and from parental interviews whereas externalizing behavioral problems were assessed by psychiatrist according to diagnostic and statistical manual of mental disorders (DSM) 5. The frequency and severity of externalizing disorders were analyzed by chi-square test and paired-t test and p value d” 0.05 was significant. Data analysis was done by statistical package for social sciences (SPSS) version 26. The results showed that, among the cases 48.9% were within 10-14 years and male were 79.1%. The present study showed that attention deficit hyperactivity disorder (ADHD) was present among 54.1% of cases, oppositional defiant disorder (ODD) was present among 19.4% of cases, and conduct disorder was present among 5.1% of cases whereas 21.4% were suffering from both ADHD and ODD. Obstetric complications had no significant association with externalizing disorders. A little was known about the association between birth complications and externalizing behavior. The study revealed no significant association between birth complications and externalizing behavior. So steps were required to rule out other factors which might contribute significant role to develop externalizing disorders. Bang J Psychiatry 2020; 34(2): 20-24